Microstructured silicon carbide neutron detectors - Cooper, Brian W (Kansas State University, 2019)
Silicon carbide is a material of interest in many ventures as an intriguing semiconducting material for use as high voltage, high temperature, high power, or high frequency devices. Silicon carbide is physically extremely tough and durable and is also very chemically resistant. The work presented here details using silicon carbide (SiC) as the semiconducting substrate for a high-efficiency neutron detector. The work begins with the fabrication of planar SiC neutron detectors utilizing ¹⁰B as the neutron conversion material. The SiC substrate was patterned via photolithography techniques prior to the deposition of an etchant mask. The following materials were used as etchant mask materials; nickel, indium tin oxide, and aluminum. The SiC devices were plasma etched using SF₆ based gas chemistries. The desired trench profile was 4 microns wide with desired depth between 10 and 20 microns. The formation of microfeatures within the trenches was observed during several etching trials as well as the trench profile narrowing to a point. After etching, titanium/gold contacts were fabricated using e-beam evaporation and various masking techniques. Next the devices were electrically tested for leakage current and capacitance. Typical leakage current was <10 pA at 100 V applied bias with a capacitance of <10 pF. Then the devices were backfilled with enriched ¹⁰B powder. The backfilled devices were tested with alpha particles, gamma rays, and neutrons. The neutron sources used were ²⁵²Cf and the Kansas State University TRIGA Reactor diffracted beamport. The devices proved to have low gamma sensitivity with respect to neutrons. When the devices were irradiated by high-activity alpha particle sources, significant charge trapping and device polarization was observed. The initial devices were 10 mm x 10 mm, but due to complications during the etchant mask formation, the device size was changed to 5 mm x 5 mm. The 5 mm x 5 mm devices were tested for neutron sensitivity using the ²⁵²Cf source and the diffracted beamport. Thermal neutron efficiency of 2.28±0.031% was measured. The final SiC wafer was patterned with the top contact and etchant mask. However, during dicing, the layers delaminated and peeled of the SiC substrate. Substantial efforts were made to pattern the remaining partial wafer to little success.
Keywords: Silicon carbide; Neutron; Neutron detector; Plasma etching